Latest research at the advanced displays laboratory at NTU - Surman, Phil (2020)
There are many basic ways of providing a glasses-free 3D display and the three methods considered most likely to succeed commercially were chosen for our current research, these are; multi-layer light field, head tracked and super multiview displays. Our multi-layer light field display enables a far smaller form factor than other types, and faster algorithms along with horizontal parallax-only will considerably speed-up computation time. A spin-off of this technology is a near-eye display that provides focus cues for maximizing user comfort. Head tracked displays use liquid crystal display panels illuminated with a directional backlight to produce multiple sets of exit pupil pairs that follow the user's eyes under the control of a head position tracker. Our super multiview display (SMV) system uses high frame-rate projectors for spatio-temporal multiplexing that give dense viewing zones with no accommodation/convergence (A/C) conflict. Bandwidth reduction is achieved by discarding redundant information at capture. The status of the latest prototypes and their performance is described; and we conclude by indicating the future directions of our research.